2020
DOI: 10.1007/s43465-020-00282-5
|View full text |Cite
|
Sign up to set email alerts
|

Management of Traumatology Patients During the Coronavirus (COVID-19) Pandemic: Experience in a Hub Trauma Hospital in Northern Italy

Abstract: Background As a result of the uncontrolled spread of the COVID-19 virus infection, a health reorganization according to the “hub and spoke” model was necessary. The purpose of the article was to document the adopted corporate protocol and describe the management of the traumatized patient in a Hub center. Methods Our hospital has been identified as one of the three regional Hubs for polytrauma and major traumas, requiring suitable pathways to receive confirmed or suspected COVID-19-positive patients, from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…By contrast, other studies have reported no difference in functional outcomes for patients with hip fractures who experienced a delay in time to operation [20,21]. An increase in waiting time from presentation to operation during the pandemic has been reported by other orthopaedic and trauma departments [14,18]. The delay may reflect hospital policy to wait for a COVID-19 result before operating.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…By contrast, other studies have reported no difference in functional outcomes for patients with hip fractures who experienced a delay in time to operation [20,21]. An increase in waiting time from presentation to operation during the pandemic has been reported by other orthopaedic and trauma departments [14,18]. The delay may reflect hospital policy to wait for a COVID-19 result before operating.…”
Section: Discussionmentioning
confidence: 95%
“…An increase in waiting time from presentation to operation during the pandemic has been reported by other orthopaedic and trauma departments [ 14 , 18 ]. The delay may reflect hospital policy to wait for a COVID-19 result before operating.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Alternative explanations could be explained by staff shortages owing to contracting COVID-19. As such, the need for expediting trauma patient care while ensuring patient and staff safety is paramount in such unprecedented times [14].…”
Section: Discussionmentioning
confidence: 99%
“…Patients suffering traumatic injuries involving multiple bony regions with existing or potentially life threatening conditions is referred as polytrauma. [6,7] During this pandemic, there is critical decision making on hospital administration and individual care providers on how to conserve critical resources like N95 maks, personal protective equipment kits, oxygen beds and ICU vacancies. Half of doctors, nurses and other hospital staffs have been diverted to COVID duties.…”
mentioning
confidence: 99%